The Double-Edged Sword of Big Data in Organizational and Management Research: A Review of Opportunities and Risks - Wenzel, Ramon; Van Quaquebeke, Niels (SAGE, 2017)
While many disciplines embrace the possibilities that Big Data present for advancing scholarship and practice, organizational and management research has yet to realize Big Data’s potential. In an effort to chart this newfound territory, we briefly describe the principal drivers and key characteristics of Big Data. We then review a broad range of opportunities and risks that are related to the Big Data paradigm, the data itself, and the associated analytical methods. For each, we provide research ideas and recommendations on how to embrace the potentials or address the concerns. Our assessment shows that Big Data, as a paradigm, can be a double- edged sword, capable of significantly advancing our field but also causing backlash if not utilized properly. Our review seeks to inform individual research practices as well as a broader policy agenda in order to advance organizational and management research as a scientifically rigorous and professionally relevant field.